Systematic review of LDLR mutations associated to Familial hypercholesterolaemia evidence of functional studies and application of ACMG guidelines for FH diagnosis - Chora, J.R. (2017)
Familial hypercholesterolaemia (FH) is an autosomal dominant disorder caused by functional mutations in LDLR (>90%), APOB (5-10%) and PCSK9 (1-3%). An accurate genetic diagnosis is essential for a correct diagnosis. However it is known that only a small part of the variants identified have been characterized by in vitro functional assays. To overcome this lack of functional data the American College of Medical Genetics and Genomics (ACMG) published recently a guideline for variant interpretation in clinical settings. The propose of this review was to analyze the number of total variants in LDLR associated with FH worldwide and classify these variants’ pathogenicity by the application of ACMG variant interpretation guidelines with a special focus on functional evidence.